2017
DOI: 10.3892/etm.2017.4580
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine promotes Hsp70 and inhibits α-Synuclein accumulation in pheochromocytoma PC12 cells

Abstract: Abstract. Hsp70 regulates α-Synuclein (α-Syn) degeneration in Parkinson's disease (PD), indicating that Hsp70 promotion may be able to prevent or reverse α-Syn-induced toxicity in PD. Additionally, it has been demonstrated that glutamine (Gln) enhances Hsp70 expression. In the present study, Gln-induced Hsp70 promotion in pheochromocytoma was investigated with reverse transcription-quantitative polymerase chain reaction and western blotting methods. Then it was observed whether heat shock factor (HSF)-1 was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In addition to their role in cellular stress, they are involved in the disassembly of protein aggregates and targeting of proteins for degradation. Increasing HSP70 has been shown to inhibit α-syn accumulation in PC12 cells [ 35 ]. In this study we aimed to investigate the effects of 27-OHC on both UPS and HSP70 protein levels.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their role in cellular stress, they are involved in the disassembly of protein aggregates and targeting of proteins for degradation. Increasing HSP70 has been shown to inhibit α-syn accumulation in PC12 cells [ 35 ]. In this study we aimed to investigate the effects of 27-OHC on both UPS and HSP70 protein levels.…”
Section: Introductionmentioning
confidence: 99%
“…Glutamine, as the most abundant free amino acid, has been proved to be closely related to the occurrence and development of neurodegenerative diseases [19]. Wang et al reported that glutamine could inhibit alpha-Synuclein accumulation to protect cells against degeneration in the PD cell model [20]. In the present study, our results showed that the MPP + displayed obvious cytotoxicity on PC12 cells, while glutamine could increase the viability of PC12 cells through suppressing neurotoxicity induced by MPP + .…”
Section: Discussionmentioning
confidence: 99%
“…Ellagic acid [214] Entacapone (Comtan, ASI-6) [12,215,216] Enzastaurin [164] Epicatechin [128,160,193,194] Epigallocatechin-3-gallate [117,217,218] Etidronate (HEDPA) [219] Exifone [12] F13714 [220] F15599 [220,221] Farrerol [222] Fisetin (3,3 ,4 ,7-Tetrahydroxy flavone) [223][224][225] Fraxetin [117] Galangin [226] Gallic acid and derivatives [214,227,228] Gallocatechin [128] Garcinol [229] Genistein [117,128,230,231] Glutamine [232] Glutathione derivatives [63] Glutathione -hydroxyquinoline compound [233] Glutathione-l-DOPA compound [234] Gly-N-C-DOPA [209] GSK2795039 [108] Guanabenz [235] Hesperidin [128,236] Hinokitiol […”
Section: Compound Name(s) Referencesmentioning
confidence: 99%